IMPLEMENTASI DISASTER RECOVERY PLAN SERVER SYSTEM DENGAN METODE FAILOVER DAN MIRRORING CO-LOCATION SERVER BERBASIS LINUX DI FAKULTAS KEDOKTERAN UNISSULA (Information Technology and Telematics, 2016)
Availability backup server so sustain the smooth College in providing services and to apply the system DRP (Disaster Recovery Plan) at FK UNISSULA to secure the risk of data loss due to a disaster and to improve the High Availability Data Center owned, and providing our academic information systems are up to date. System backup server content which we did using the methodology of offsite backup server where the server crashes anticipation method by placing the backup server in a different location from the main server , and the system will automatically failover backup server will replace the role of the primary server if the primary server is down . Server failover clustering system that was built to work well based on testing that has been done where if one server either physically or network can not be accessed , the user can still access the data and application server on the backup server . The process of synchronizing data between the main server and backup server can run well and realtime by using the master database replication methods and response time to master server failover from the primary server to the backup server is shorter compared to the process of recovery from the primary server to the backup server . The end result of this research is the implementation of the technique failover cluster server network using a VPN can be a solution of the Faculty of Medicine Unissula for applying the disaster recovery system is safe , because the backup server can be located anywhere and with the level of security access high because it uses private network ( VPN ) .